Come in, who is it?: the predisposition of the social economy to the circular economy - Pereira, Augusta (2020)
The main objective of the study is to analyse the predisposition of social economy agents to share resources. To answer the objective, we opted for a qualitative exploratory approach directed to managers and a quantitative exploratory approach directed at employees. The results showed that they have a significant economic impact on quantity, paid work and turnover (CESE, 2017). We have measured the relationship between the demonstration of interest in sharing and qualification appropriate to the function of managers and employees. It was verified the practice of informal and unregulated sharing of own and other resources, between local partners, without a model of knowledge management, assets, time, use/reuse and use. It is hoped that the study could serve as a scientific/methodological basis for a regional investment, R&D and partnership project, combining the interest in a smart region and applying the principles of circular economy.